Discursive translations of gender mainstreaming norms: The case of agricultural and climate change policies in Uganda - Acosta, Mariola; Bommel, Severine van; Wessel, Margit van; Ampaire, Edidah L.; Jassogne, Laurence T.P.; Feindt, Peter (Elsevier, 2019)
While the international norm on gender mainstreaming, UN-backed since 1995, has been widely adopted in national policies, gender inequalities are rarely systematically addressed on the ground. To explain this limited effectiveness, this paper takes a discourse analytical perspective on gender policy and budgeting, with a focus on the translation of the international norm into domestic norms and policies. An in-depth, inductive analysis of 107 policy documents in Uganda examines how the gender mainstreaming norm has been translated at three administrative levels: national, district, sub-county. The analysis finds five processes that reduce the norm's transformational potential: neglecting gender discourse, gender inertia, shrinking gender norms, embracing discursive hybridity and minimizing budgets. Overall, gender mainstreaming largely stopped at the discursive level, and often paradoxically depoliticized gender. The findings explain why gender mainstreaming might be helpful but not sufficient for advancing gender equality and suggest additional focus on promising practices, women's rights movements and stronger monitoring.